Fibre distribution in the lungs and pleura of subjects with asbestos related diffuse pleural fibrosis. Issue 11 (November 1991) - Gibbs, A R; Stephens, M; Griffiths, D M; Blight, B J; Pooley, F D
Abstract : The lungs from 13 cases of diffuse pleural fibrosis associated with a history of exposure to asbestos were examined. Samples were taken from the visceral pleura and central and subpleural zones of the lungs for histopathological and mineralogical studies. The fibre type, size, and number were estimated for each of these regions by transmission electron microscopy and energy dispersive x ray analysis. Amphibole fibre counts were raised when compared with a non-occupationally exposed group and matched those seen in cases of pleural plaques, mild asbestosis, and mesothelioma. A wide case to case variation of distribution was seen. No significant difference was apparent between central and subpleural zones, whereas low asbestos counts were found in the pleura; these were mainly short chrysotile fibres. Within the lungs more (45%) of the longer (greater than 4 microns) and thinner (less than 0.25 micron) amphibole fibres were retained in keeping with other studies implicating such fibre profiles in the pathogenesis of asbestos related disease.